A Comparative Study of Metakaolin/Slag-Based Geopolymer Mortars Incorporating Natural and Recycled Sands - Saliha Benalia; Leila Zeghichi; Zied Benghazi (Salehan Institute of Higher Education, 2022)
Great efforts are being made to minimize the negative impact of the Portland cement industry on the environment by using industrial by-products during the manufacture of clinker or by the partial replacement of cement during the preparation of concrete. However, the carbon footprint remains relatively high in addition to the large consumption of natural resources such as sand and other aggregates. A solution to these problems is to completely replace Portland cement with a new generation of mineral binders, commonly known as geopolymers, which have properties similar to those of Portland cement. These binders can be obtained by the alkali-activation of siliceous or aluminosilicate materials. This study aims to develop pozzolanic type binders at room temperature (20°C) from the alkali-activation of aluminosilicate materials based on metakaolin and blast furnace slag at different percentages. Different activators were employed, including solid (NaOH) and liquid (Na2SiO3.nH2O). The optimal mixtures were used for making mortars based on natural sand (NS) and concrete recycled sand (CRS). A comparative experimental study of the physical, mechanical, and microstructural characteristics of the two types of mortars was conducted. Cement mixtures with a high amount of slag and an association of sodium hydroxide and sodium silicate gave the best physico-mechanical properties. A drop in the compressive strength of mortars prepared with CRS was observed after 365 days, but it was still higher than those with NS. The obtained results show the possibility of designing an eco-friendly CRS-based geopolymer mortar that is more resistant than NS-based mortar with a homogeneous and integrated microstructure. Doi: 10.28991/CEJ-2022-08-08-07 Full Text: PDF